2021
DOI: 10.21203/rs.3.rs-870525/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Psychosocial Distress on the Quality of Life of Cancer Patients in Two Health Facilities in Cameroon

Abstract: Background: Psychosocial distress interferes with the ability to cope effectively with cancer, its physical symptoms and treatment. This in turn leads to poor outcomes in patients. Objective: The aim of this study was to investigate the impact of psychosocial distress on the quality of life of cancer patients in two health facilities in Cameroon. Methods: This study used a cross-sectional hospital-based design. The study was carried out over a period of three months from July-September 2020. The sample size wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 14 publications
(33 reference statements)
3
5
0
Order By: Relevance
“…The median age of our study population was 54 years, which is similar to studies performed in Africa that have documented age between 46 and 54 years but lower than the west where the mean age reported is between 58 and 68 years. [10,[21][22][23]32,33] The female predominance observed in this study reflects similar findings from studies in Africa and the West. Breast cancer was the leading diagnosis at 26% followed by cervical cancer at 24% which mirrors the Kenyan national distribution of all cancers as reported in Globocan 2020.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The median age of our study population was 54 years, which is similar to studies performed in Africa that have documented age between 46 and 54 years but lower than the west where the mean age reported is between 58 and 68 years. [10,[21][22][23]32,33] The female predominance observed in this study reflects similar findings from studies in Africa and the West. Breast cancer was the leading diagnosis at 26% followed by cervical cancer at 24% which mirrors the Kenyan national distribution of all cancers as reported in Globocan 2020.…”
Section: Discussionsupporting
confidence: 90%
“…[21,23] The mean distress score in our patients was similar to that in other studies with a range of 2.47-4.7 but much lower than that in studies conducted in palliative settings where more than 70% of patients had high levels of distress. [21][22][23]32,[35][36][37] In our study, ECOG performance status was the only factor associated with distress similar to what a Nigerian study showed. [22] Other studies have reported being female, type of malignancy, being on chemotherapy, or under palliative care as independent predictors of distress.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A total of 44 studies were identified in this category across SSA. The majority of studies reported that the burden of unmet psychosocial needs was between 20% and 90.4% among adult cancer patients 24–27 . Psychosocial issues commonly reported in most of the studies were related to physical strength, 28 emotional distress, 29–31 anxiety and depression, 29,32–38 sub‐optimal pain control, 39 body image/body issues (abnormal body sensations, feelings of unattractiveness, poor self‐esteem), 28,40–46 health information need, 47–49 support system lack, 45,50 relationship disruptions (e.g., rejection of sexual activities from their spouse, changes in the work role etc.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies reported that the burden of unmet psychosocial needs was between 20% and 90.4% among adult cancer patients. [24][25][26][27] Psychosocial issues commonly reported in most of the studies were related to physical strength, 28 emotional distress, [29][30][31] anxiety and depression, 29,[32][33][34][35][36][37][38] sub-optimal pain control, 39 -91…”
Section: Theme 1: Psychosocial Needs Of Adult Patients With Cancer In...mentioning
confidence: 99%